For all peoples : A biblical theology of missions in the Gospels and Acts - Keener, Craig S., 1960- (Baguio City, Phillippines Asia Pacific Theological Seminary Press, 2020)
Given this unique locus of today's church, this book takes us back to the foundational teachings of Jesus on missions: the Great Commission (gospel of Matthew) and the Messianic Commission (Gospel of John). Although these two passages are "universal" in grounding Christian mission, Professor Keener wants to assure that the role of the Holy Spirit is central to Christian living and acting as God's witnesses.
Keywords: Missions -- Biblical teaching